Breakfast Skipping in a Multi-Ethnic Population of Middle-Aged Men and Relationship With Sociodemographic Variables and Weight Status - AlFaris, Nora A.; Alshwaiyat, Naseem M.; Alkhalidy, Hana; Alagal, Reham I.; AlTamimi, Jozaa Z.; AlKehayez, Nora M. (Frontiers in Nutrition, 2022)
Background: Breakfast eating is regarded to be necessary for maintaining a healthy body weight. On the other hand, breakfast skipping has been linked with obesity incidence. This study was carried out to determine the prevalence of breakfast skipping among a multi-ethnic group of middle-aged men living in Saudi Arabia and the association between breakfast skipping and sociodemographic variables and weight status. Methods: This cross-sectional study included 1800 middle-aged men aged 36 to 59 years. Participants' sociodemographic information and frequency of breakfast eating were obtained through personal interviews. The body mass index was determined after measuring body weight and height using standardized methods. Results: The prevalence of breakfast skipping was 42.1% of the study participants. Nationality was a predictor of breakfast skipping. Bangladeshi participants (N = 100) have the lowest rate of breakfast skipping (9.0%), whilst Saudi participants (N = 161) have the highest rate (73.3%). Weight status was another predictor of breakfast skipping as breakfast skippers had a significantly higher average body mass index (27.1 ± 3.8) than breakfast consumers (26.2 ± 3.5). Overweight/obese participants have a significantly higher breakfast skipping rate (44.9%) than participants with underweight/normal weight (36.6%). Conclusion: The rate of breakfast skipping is relatively high among middle-aged men living in Saudi Arabia. The data support a link between breakfast skipping and sociodemographic variables and weight status.